Kewenangan Mengadili Dalam Penyelesaian Perkara Kepailitan dan Penundaan Kewajiban Pembayaran Utang Perbankan Syariah - Kartika, Sahnaz; Harahap, Muhammad Yadi (Fakultas Syariah INSURI Ponorogo, 2023)
The Religious Courts are the only legal institution authorized to resolve sharia economic disputes, based on Law Number 3 of 2006 concerning Religious Courts. This is also supported by Supreme Court Regulation Number 14 of 2016 concerning Procedures for Settlement of Sharia Economic Cases. However, there are still many sharia business/shariah banking cases in commercial courts where legal submissions are tug-of-war in a dichotomy between the absolute competence of the Religious Courts and submission to the authority of the commercial court within the district court environment. So that there is regulatory disharmony and legal uncertainty regarding jurisdictional decisions in bankruptcy cases of Islamic economic institutions. This research method uses normative research by examining legal materials related to bankruptcy and PKPU. The results of the study indicate that it is necessary to unify and harmonize regulations that specifically regulate the settlement of sharia bankruptcy cases so that there are no jurisdictional conflicts between the Religious Courts and the Commercial Courts. Legal consequences if the bankruptcy case of Islamic banking is still filed at the Commercial Court, there will be coercion of the substance of sharia economic law to become conventional economic law, so that the settlement of the dispute is not in sync with the contract and the concept of settlement of cases which prioritizes business concepts and business continuity rather than fairness and certainty. substantive.